Penerapan Metode AHP pada Penentuan Sales Terbaik Studi Kasus: PT. Sampoerna Telekomunikasi Indonesia - Imron Imron (JURNAL TEKNIK KOMPUTER, 2019)
Competition in various business sectors between companies cannot be avoided. One of the supporters of the success of various aspects of the work of the company is human resources, which is one of the assets of the company that runs the wheels of the business movement. An example of an aspect that always becomes competition between companies is the sale of a product created by each company. One of the supporters of the success of selling a product in the company is sales. The number of products sold depends on how the sales can market the product. So it requires talented sales people to attract new customers, increase product sales, and increase customer satisfaction. Therefore leaders must be able to assess the capabilities of salespeople in marketing the company's products. So that leaders can determine which sales can be maintained and which ones need to be replaced. AHP is one of the tools (processes) in decision making. This procedure is so powerful that it has been widely applied in important decision making. AHP can be relied on, because in AHP a priority is composed of various choices that can be in the form of criteria that have been previously decomposed (structure) first, so that priority setting is based on a structured (hierarchical) process and makes sense